2015
DOI: 10.1080/21683565.2015.1073206
|View full text |Cite
|
Sign up to set email alerts
|

Variability of On-Farm Food Plant Diversity and Its Contribution to Food Security: A Case Study of Smallholder Farming Households in Western Kenya

Abstract: Traditional mixed agroforestry farms are regarded as sustainable agroecological systems contributing to agrobiodiversity conservation and household food and nutrition security in subSaharan Africa. However, in Kenya little is known on the level of agrobiodiversity of these mixed farms and its contribution to food and nutrition security. A case study was conducted to assess food plant and livestock diversity and to identify the biophysical and socio-economic factors influencing food plant diversity in 30 smallh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 50 publications
3
26
1
1
Order By: Relevance
“…Temperatures are moderate ranging from 12 to 26 °C. Embu soils are sandy clay in nature characterized by low exchangeable ions and have low percentage nitrogen content (% N) of 0.23 % [4]. Majority of the households are smallholder farmers with small units of crops and livestock.…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperatures are moderate ranging from 12 to 26 °C. Embu soils are sandy clay in nature characterized by low exchangeable ions and have low percentage nitrogen content (% N) of 0.23 % [4]. Majority of the households are smallholder farmers with small units of crops and livestock.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Smallholder farmers in most areas such as Eastern Kenya highly depend on crop diversity and livestock enterprises due to the limitation of farm sizes [4]. Embu and Tharaka-Nithi counties are close to the slopes of Mt.…”
mentioning
confidence: 99%
“…Agrobiodiversity factors into social prestige. Farmers with more trees and crops tend to be wealthier and older (but not necessarily have larger farms), and wild foods tend to have low status (Ng'endo et al 2015). However, Ng'endo et al (2015) and Connelly and Chaiken (2000) found that agrobiodiversity was no guarantee of food or financial security.…”
Section: Discussionmentioning
confidence: 99%
“…As a main food staple in Kenya, maize was a crop that farmers would have liked to plant if it could grow well alongside Eucalyptus sp. (Ng'endo et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Associadas a locais como "hotspots" (Myers et al, 2000), estão populações tradicionais que, historicamente, têm estabelecido uma relação íntima de interação com o meio natural, a partir da qual é gerado um tipo de conhecimento como resultado de sua adaptação ao ecossistema. Baseado nesse conhecimento local, elas praticam uma forma de agricultura caracterizada por apresentar elevada diversidade inter e intra específica de plantas cultivadas (Peroni & Martins, 2000;Bernholt et al, 2009;Brussaard et al, 2010;Ratnadass et al, 2012;Ng'endo et al, 2015;Shen et al, 2017). Dessa forma, essas populações criam formas de manejo de áreas na qual tais práticas de manejo estão profundamente ligadas à continuidade dos processos naturais do meio (Saxena et al, 2016), considerado, assim, um sistema socioecológico 1 .…”
Section: Introductionunclassified